Neuronal differentiation potential of primary and immortalized adipose stem cells by photobiomodulation - George, Sajan; Hamblin, Michael R.; Abrahamse, Heidi (Journal of photochemistry and photobiology. B, Biology, 2022)
Adipose Stem Cells (ASCs) are capable of neuronal differentiation, which makes them an ideal choice for therapies in nerve injuries. Principally, the differentiation of autologous ASCs to neurons offers solutions for the replacement therapies of nervous system with patient's own genetic background. On the contrary, the use of genetically modified (immortalized) ASCs has the benefit of accessibility by surpassing ethical concerns and ease for propagation as a continuous cell culture. Photobiomodulation (PBM) is a therapeutic modality with laser or light, which is widely been used for modulating stem cell bioprocesses viz. proliferation and differentiation. A comparative analysis was performed to evaluate the neuronal differentiation potential of primary ASCs isolated from a healthy human subject with commercially obtained immortalized ASCs with PBM. The outcome of this analysis will help us to know either primary or immortalized ASCs are most suitable for biomedical applications. Both primary and immortalized ASCs were characterized using their surface protein markers CD44/90/133/166 and induced to differentiate into neuronal cells using Fibroblast Growth Factor, basic (bFGF) and forskolin following PBM using Near Infra-Red (NIR) lasers. Based on the expression of nestin, an early neuronal marker an exposure to 5, 10 and 15 J/cm2 of NIR and growth inducers for 14 days the primary ASCs demonstrated a higher neuronal differentiation potential compared to the immortalized ASCs. However, newly differentiated cells from either of these ASCs did not reveal βIII-tubulin, an intermediate neuronal marker even by 21 days of differentiation. This study gives an indication that immortalized ASCs have a phenotype and differentiation potential slightly less but comparable to the freshly isolated ASCs. We suggest that PBM along with growth inducers offer a better solution of differentiating ASCs to neurons. [Display omitted] •Photobiomodulation can differentiate primary human adipose-derived stem cells (ASCs) to neuronal cells.•Neuronal differentiation of primary human ASCs is achievable by near infrared laser of 825 nm.•A significant increase in neuronal differentiation is achievable using 5, 10 and 15 J/cm2 at 825 nm.•Photobiomodulation-induced differentiation potential of primary human ASCs is higher than in immortalized human ASCs.